Comparison of prediction accuracies between mathematical models to make projections of confirmed cases during the COVID-19 pandamic by country/region. Issue 50 (17th December 2021) - Tsai, Kang-Ting; Chien, Tsair-Wei; Lin, Ju-Kuo; Yeh, Yu-Tsen; Chou, Willy
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The COVID-19 pandemic caused >0.228 billion infected cases as of September 18, 2021, implying an exponential growth for infection worldwide. Many mathematical models have been proposed to predict the future cumulative number of infected cases (CNICs). Nevertheless, none compared their prediction accuracies in models. In this work, we compared mathematical models recently published in scholarly journals and designed online dashboards that present actual information about COVID-19. Methods: All CNICs were downloaded from GitHub. Comparison of model R 2 was made in 3 models based on quadratic equation (QE), modified QE (OE-m), and item response theory (IRT) using paired- t test and analysis of variance (ANOVA). The Kano diagram was applied to display the association and the difference in model R 2 on a dashboard. Results: We observed that the correlation coefficient was 0.48 ( t = 9.87, n = 265) between QE and IRT models based on R 2 when modeling CNICs in a short run (dated from January 1 to February 16, 2021). A significant difference in R 2 was found ( P < .001, F = 53.32) in mean R 2 of 0.98, 0.92, and 0.84 for IRT, OE-mm, and QE, respectively. The IRT-based COVID-19 model is superior to the counterparts of QE-m and QE in model R 2 particularly in a longer period of infected days (i.e., in the entire year in 2020). Conclusion: An online dashboard was demonstrated to display the association and difference in prediction accuracy among predictive models. The IRT mathematical model was recommended to make projections about the evolution of CNICs for each county/region in future applications, not just limited to the COVID-19 epidemic.